Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure, let's simplify the given polynomial step by step and then evaluate it for [tex]\( x = -2 \)[/tex] and [tex]\( y = -3 \)[/tex].
1. Combine like terms in the polynomial:
The given polynomial is:
[tex]\[ 2xy^2 + 3x - 4y^2 + 2xy^2 - 3xy^2 - x \][/tex]
Let's group the like terms:
[tex]\[ (2xy^2 + 2xy^2 - 3xy^2) + (3x - x) - 4y^2 \][/tex]
Combine the [tex]\( xy^2 \)[/tex] terms:
[tex]\[ (2 + 2 - 3)xy^2 + (3 - 1)x - 4y^2 \][/tex]
[tex]\[ xy^2 + 2x - 4y^2 \][/tex]
So, the simplified polynomial is:
[tex]\[ xy^2 + 2x - 4y^2 \][/tex]
2. Evaluate the simplified polynomial for [tex]\( x = -2 \)[/tex] and [tex]\( y = -3 \)[/tex]:
Let's substitute [tex]\( x = -2 \)[/tex] and [tex]\( y = -3 \)[/tex] into the simplified polynomial:
[tex]\[ (-2)(-3)^2 + 2(-2) - 4(-3)^2 \][/tex]
3. Compute each term separately:
- For the term [tex]\( xy^2 \)[/tex]:
[tex]\[ (-2)(-3)^2 = (-2)(9) = -18 \][/tex]
- For the term [tex]\( 2x \)[/tex]:
[tex]\[ 2(-2) = -4 \][/tex]
- For the term [tex]\( -4y^2 \)[/tex]:
[tex]\[ -4(-3)^2 = -4(9) = -36 \][/tex]
4. Add the computed values:
[tex]\[ -18 + (-4) + (-36) \][/tex]
Combine the values:
[tex]\[ -18 - 4 - 36 = -58 \][/tex]
So, the value of the polynomial [tex]\( 2xy^2 + 3x - 4y^2 + 2xy^2 - 3xy^2 - x \)[/tex] when evaluated for [tex]\( x = -2 \)[/tex] and [tex]\( y = -3 \)[/tex] is [tex]\(-58\)[/tex]. Additionally, the individual contributions to the result are [tex]\(-18\)[/tex], [tex]\(-4\)[/tex], and [tex]\(-36\)[/tex] respectively.
1. Combine like terms in the polynomial:
The given polynomial is:
[tex]\[ 2xy^2 + 3x - 4y^2 + 2xy^2 - 3xy^2 - x \][/tex]
Let's group the like terms:
[tex]\[ (2xy^2 + 2xy^2 - 3xy^2) + (3x - x) - 4y^2 \][/tex]
Combine the [tex]\( xy^2 \)[/tex] terms:
[tex]\[ (2 + 2 - 3)xy^2 + (3 - 1)x - 4y^2 \][/tex]
[tex]\[ xy^2 + 2x - 4y^2 \][/tex]
So, the simplified polynomial is:
[tex]\[ xy^2 + 2x - 4y^2 \][/tex]
2. Evaluate the simplified polynomial for [tex]\( x = -2 \)[/tex] and [tex]\( y = -3 \)[/tex]:
Let's substitute [tex]\( x = -2 \)[/tex] and [tex]\( y = -3 \)[/tex] into the simplified polynomial:
[tex]\[ (-2)(-3)^2 + 2(-2) - 4(-3)^2 \][/tex]
3. Compute each term separately:
- For the term [tex]\( xy^2 \)[/tex]:
[tex]\[ (-2)(-3)^2 = (-2)(9) = -18 \][/tex]
- For the term [tex]\( 2x \)[/tex]:
[tex]\[ 2(-2) = -4 \][/tex]
- For the term [tex]\( -4y^2 \)[/tex]:
[tex]\[ -4(-3)^2 = -4(9) = -36 \][/tex]
4. Add the computed values:
[tex]\[ -18 + (-4) + (-36) \][/tex]
Combine the values:
[tex]\[ -18 - 4 - 36 = -58 \][/tex]
So, the value of the polynomial [tex]\( 2xy^2 + 3x - 4y^2 + 2xy^2 - 3xy^2 - x \)[/tex] when evaluated for [tex]\( x = -2 \)[/tex] and [tex]\( y = -3 \)[/tex] is [tex]\(-58\)[/tex]. Additionally, the individual contributions to the result are [tex]\(-18\)[/tex], [tex]\(-4\)[/tex], and [tex]\(-36\)[/tex] respectively.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.